Intimate partner violence, traditional attitudes and alcohol use in Serbia - Dragišić-Labaš Slađana (Crimen (Beograd), 2019)
This paper explores the link between alcohol use and traditional family attitudes in the context of intimate partner violence against women in Serbia. This form of violence can be understood as a way to consolidate and preserve power against women. A feminist approach is hence significant in dealing with this serious social problem. According to feminist theories that we refer to, physical force serves to establish control and is considered the most important male resource of power, especially in patriarchal societies. Power is understood as structurally conditioned and supported. For centuries, access to "kafanas" (pubs) and alcohol consumption has been granted exclusively to men. Alcohol use and physical force thus became the most important resources of male power, especially because violence supported by alcohol use was justified and almost taken as a given within the domestic sphere. Still today, traditional family attitudes further support violent behavior, preventing the victims from reporting abusers. The survey on violence against women was conducted on a sample of 2406 women aged 18-75. A sample of families with alcohol problems was identified (211) and compared to the sample that did not include alcohol use (2195). The findings confirmed a significant association of partner violence with alcohol use and the infrequency of reporting partner abuse by victims who support traditional attitudes. Male abusers who consume alcohol and traditionally socialized female victims together maintain a dysfunctional marital dyad.